Narratives and Comparisons Adversaries or Allies in Understanding Science? - Carrier, Martin; Mertens, Rebecca; Reinhardt, Carsten (2021)
As a powerful tool in the production of knowledge, comparing plays a crucial part in the sciences and the humanities. This volume explores the relationship between comparing and narrating in epistemic practices and clarifies the ways in which narratives enable or impede practices of comparing. It takes into account related activities, such as measuring and classifying, modeling, establishing norms and categories, as well as organizing and popularizing knowledge, to analyze the ambivalent relationship between narratives, scientific explanation, and understanding. The contributions bring out the epistemic role of narratives, and elucidate how narratives are connected to comparisons and scientific explanations.